Trastorno del espectro autista y las dinámicas familiares en niños entre los 7 a 9 años de la ciudad de Babahoyo - Moncayo Medina, Saray Lorena (2025)
This study examines the correlation between family dynamics and autism in children aged 7 to 9 years. In addition, the research sought to explore how the presence of children with autism affects family functioning through a comprehensive assessment using the FF-SIL and FACES IV questionnaires as well as an interview focused on autism-related behaviors. The study identified significant relationships between family cohesion, communication, and satisfaction with various aspects of the development of children with autism. The results show that cohesive and flexible family environments are closely associated with better social and communication skills in children, on the other hand, a higher level of satisfaction within the family is correlated with better language understanding and fewer behavioral difficulties, this suggests that the family environment plays a crucial role in fostering the development of children with autism, it also highlights the importance of maintaining family harmony and emotional support in managing autism-related challenges. The study offers insight into how different family dynamics can influence the behavioral and developmental outcomes of children with autism, emphasizing the need for interventions aimed at promoting cohesion. and family flexibility